Mobile-based wide area pest surveillance and advisory services for horticultural crops in Haryana - SINGH, NIRANJAN; SARDANA, H R; BHAT, M N; CHOUDHARY, MANOJ; KHOKHAR, M K; KUMAR, HARISH (The Indian Journal of Agricultural Sciences, 2022)
The development and implementation of ICT based pest monitoring and advisory system was an innovative idea to speed up the process of providing timely and correct pest management advice to the farmers. The system captured a total of 20,754 pest incidence, recorded through pest-specific scientific methods during 2018–20 and produced reports of pest status in farmer fields vis-a-vis pest ETL. Based on these pest reports, experts submitted 1,971 pest management advisories into the system which were disseminated to 7000 registered farmers of 9 districts of the state, through 4,49,465 SMSs during the years. The timely availability of correct pest management information greatly helped in minimising crop losses. The system also helped in the quick identification of pest hot spot areas and thus preparing the state agencies to effectively manage the pest problems in those areas. This also helped in the promotion and awareness of integrated pest management among the farmers. Implementation of appropriate pest management strategies by the farmers led to increasing in crop yield and avoidance of pest epidemics during the period. Besides, the system created a centralised pest data repository which could be utilised for drawing inferences in future. Such a database combined with a weather database could be a potential source for the development of forewarning models of insects and diseases.